BUDAYA PATRIARKI DALAM NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL-SAADAWI DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM - Aulia, Nessa Izzati; Arifin, Mohamad Zaenal; Ibrahim, Dede (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to explore the forms of patriarchal culture that are explicitly contained in the novel Perempuan di Titik Nol by Nawal El Sadaawi. Most patriarchal systems generally place men in high-ranking roles and possess dominant authority within the social order. This has a significant impact on the marginalization of women's status and contributions. This research is qualitative with a descriptive analytical approach. Primary data was obtained from Nawal El-Saadawi's novel "Woman at Point Zero," while secondary data were sourced from books, journal articles, theses, and other relevant documents. The obtained data were then analyzed using content analysis techniques. This study found that the patriarchal culture alluded to in the novel frequently occurs in both domestic and public spheres. Domestic patriarchy is based on the belief that housework is a woman's natural duty. This is reflected in the experiences of the central character, Firdaus, who experiences violence, sexual exploitation, and repeated betrayal from men throughout her life. Public patriarchy is evident in social structures, from the community, workplace, and even the state level. This study concludes that the educational values ​​in Nawal El-Saadawi's novel Perempuan Di Titik Nol (Woman at Point Zero) are not always presented in the form of direct teachings, but rather through the drawing of wisdom and learning from the experiences of Firdaus, the central character. Islamic education emphasizes the importance of building monotheism so that humans are not enslaved by lust, power, and material possessions. Islamic education also emphasizes the importance of respecting and recognizing the potential and contributions of each gender fairly and equally.